BUILD THE SOUL ENTREPRENEUR FROM AN EARLY AGE AS A MEANS OF CREATING A GENERATION KHOIRU UMMAH WITH THE EXISTENCE OF A SUPERIOR HUMAN RESOURCES - Anas Rangga (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
In the face of the current era and the next era, challenges that currently applies is the readiness of human resources in relation to how the progress of this land to the future. Khairu ummah in the language means the best people, in the current context of the generation that capable to manage themselves and able to resolve the matter of life to support life akherat. Conceptually, "superior human resources” is one inside compartment. This paper is a review of the literature based research. Therein will be examined how to build a generation of khairu ummah namely superior human resources, with the planting of the soul entrepreneur from an early age. The purpose of this study is to know the efforts that need to be done in the building of the soul entrepreneur on the early childhood. So if the effort done, it is expected that the children will grow and develop into the quality of human resources as well as the generation of khairu ummah, which is part of the khalifatullah to manage the wealth of natural resources in the earth and promote this nation.